Spalling behaviours of railway wheel under cyclic loading - Thong, Pak Loong (Nanyang Technological University, 2020)
Railway transport Industry is very important and crucial in the 21th century as it played a vital role in the country economic growth. Whenever there is a railway accident it would cause lots of disruption which will affect the country economic growth. One of the major causes of railway accident is caused by derailment due to rolling contact fatigue(RCF). RCF happened due to traction and surface contact forces leading to plastic deformation which led to the formation of white etching layer (WEL). In recent years, railway wheel white etching layer (WEL) have become a point of interest for research purposes on its characteristic and behaviour under cyclic loading. This project will show how crack angle and crack propagation areco-related. By simulation and understanding, it will give us data on how to avoid and prevent such failure from happening as well as the maintenance of railway and wheel efficiently. The software ABAQUS will be used to perform simulation on crack propagation in a railway wheel using the software function Extended Finite Element Method (XFEM). The main goal of this project is to conduct simulation and establish the relationship between crack propagation and crack growth length and as well as wheel materials.